Optimal Allocation of FACTS Devices Using Kinetic Gas Molecular Optimization and Cuckoo Search Algorithm - Bhayani, Kishan Jivandas; Pandya, Dharmesh J. (Journal of the Institution of Engineers (India). Series B, Electrical Engineering, Electronics and telecommunication engineering, Computer engineering, 2022)
Recently, voltage instability is considered as a key issue in the transmission line system due to its dynamic load pattern and increasing load demand. Flexible AC transmission systems (FACTS) devices are exploited to conserve the instability of voltage by controlling real and reactive power over the transmission system. In the transmission network, the size and position of FACTS are important considerations to provide a proper power flow in the system. In this paper, optimal sizing and assignment of FACTS are carried out by combining the kinetic gas molecular optimization (KGMO) and cuckoo search algorithm (CSA). There are three different FACTS devices used, namely Static VAR compensator, Thyristor Controlled Series Compensator and Unified Power Flow Controllers. The major objective functions of the proposed hybrid KGMO-CSA method are minimizing the installation cost, total voltage deviation (TVD), Line Loading and real power loss. Moreover, the optimal placement using the hybrid KGMO-CSA method is validated in MATLAB software by analyzing IEEE 14-, 30- and 57-bus system. Finally, the hybrid KGMO-CSA achieved 3.6442 MW power loss and 0.1007 p.u. TVD which is less when compared to existing quasi-oppositional chemical reaction optimization (QOCRO).